C-terminal binding protein-2 triggers CYR61-induced metastatic dissemination of osteosarcoma in a non-hypoxic microenvironment - Laura Di Patria; Nadia Habel; Robert Olaso; Romain Fernandes; Catherine Brenner; Bojana Stefanovska; Olivia Fromigue (Journal of Experimental & Clinical Cancer Research)
Abstract Background Osteosarcoma is the most prevalent cancer-related bone disease diagnosed in the pediatric age group. The rapid development of metastatic lesions and resistance to chemotherapy remain major mechanisms responsible for the failure of treatments and poor outcome. We established that the expression level of Cysteine-rich protein 61 (CYR61/CCN1) correlates to tumor neo-vascularization and dissemination in preclinical and clinical osteosarcoma samples. The aim of this study was to investigate the CYR61-related mechanisms leading to the acquisition of metastatic capacity by osteosarcoma cells. Methods Transcriptomic data issued from RNA-seq were subjected to pathways and gene set enrichment analyses. Murine and human cell lines with overexpressed or downregulated C-terminal Binding protein 2 (CtBP2) were established by lentiviral transduction. Cell metabolic activity was assessed by Seahorse XF Analyzer; cell replication rate by BrdU incorporation assay; stemness by clonogenicity assay and RT-qPCR detection of markers; cell migration by wound healing assay and Boyden chambers system; cell invasion using Matrigel coated Boyden chambers or fluorescence microscopy of Matrigel embedded 3D spheroids. FFPE samples derived from syngeneic tumor cells grafts into BALB/c mice were analyzed by IHC. The protein interactome was predicted in silico using the STRING database. Results GSEA revealed that CYR61 modulate the transcription process. The in vitro expression level of CtBP2 and Cyr61 correlated positively in a panel of osteosarcoma cell lines. In silico analysis of protein–protein interaction network revealed a link with stemness markers. Variations in CtBP2 expression levels influenced stemness markers expression levels, cell clonogenicity, cell migration, Matrix Metalloproteinase activity and cell invasion. Surprisingly, while induction of CtBP2 expression under CYR61 correlated with the metastatic dissemination process in vivo, it occurred only at the invasive front of tumors. Hypoxic conditions in central tumor region interfered with CtBP2 induction of expression. Conclusions Our findings identify for the first time that CtBP2 acts as a required critical inducing factor in the CYR61-related metastatic progression of osteosarcoma, by favoring cell migration and invasiveness. Moreover, we demonstrate that while CtBP2 is a downstream transcriptional target of CYR61 signaling cascade, it occurs only under non-hypoxic conditions. The present study suggests that CtBP2 may represent a potential pivotal target for therapeutic management of metastases spreading in osteosarcoma.